2016
DOI: 10.3906/vet-1505-44
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broilers fed raw or fermented and redried wheat, barley, and oat grains

Abstract: The efficacy of diets containing 40%-50% wheat, barley, or oat grains, fermented by a solid-state fermentation process, on bird performance, carcass yield, digestive organ development, and intestinal viscosity was tested. Compared with broiler chicks fed unfermented grains, those fed fermented oats had increased feed intake, and treatment with fermented wheat and barley improved the feed conversion ratio at days 21 and 42. Treatment with fermented barley and oats resulted in increased body weight at day 42. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…It seemed that the use of eubiotic mixture 2 containing several types of active agents (probiotics, enzymes, organic acids etc.,) may induce remarkable growth promoting effects. This result confirmed all the results obtained from previous studies regarding the use of individually supplemented probiotics, enzymes and organic acids in similar cases (Ambriz-Vilchis et al, 2017;Yasar et al, 2016;Ayaşan, 2016;Elala and Ragaa, 2015;Yasar and Desen 2014;Fascina et al, 2012). Eubiotic mixture 3 was used as silage additive.…”
Section: Experiments With Eubiotic Mixturesupporting
confidence: 81%
See 2 more Smart Citations
“…It seemed that the use of eubiotic mixture 2 containing several types of active agents (probiotics, enzymes, organic acids etc.,) may induce remarkable growth promoting effects. This result confirmed all the results obtained from previous studies regarding the use of individually supplemented probiotics, enzymes and organic acids in similar cases (Ambriz-Vilchis et al, 2017;Yasar et al, 2016;Ayaşan, 2016;Elala and Ragaa, 2015;Yasar and Desen 2014;Fascina et al, 2012). Eubiotic mixture 3 was used as silage additive.…”
Section: Experiments With Eubiotic Mixturesupporting
confidence: 81%
“…The SSF was carried out at 200 L of bioreactor, using GRAS (generally regarded as safe) bacteria and yeast, to ferment the biomass under fixed conditions (pH<0.5, intermitting stirring 10 min at every 12 h, moisture content >60%, temperature=35-39 0 C), according to the modified method mentioned in the work (Yasar et al, 2016). A natural food material during the fermentation was added to coat the viable probiotic bacteria and yeast cells.…”
Section: Methods Of Eubiotic Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result clearly indicates that low water activity and high pH values (more than 5.0) are not suitable for the activation of endogenous natural microbiota of the fermenting substrate, in which the addition of exogenous microbial inoculant is necessary. Based on our recent findings (Yasar et al, 2016;Yasar and Gok, 2014), an optimised SSF process using no exogenous microbial inoculation was used to produce fermented products, which improved nutritional value in poultry. These feed materials were also good carriers for direct-fed microbial (Saccharomyces spp., and Lactobacillus spp.).…”
Section: Introductionmentioning
confidence: 99%
“…These feed materials were also good carriers for direct-fed microbial (Saccharomyces spp., and Lactobacillus spp.). The optimization of SSF process in these studies was managed under the conditions of moisture content not less than 600 g kg −1 and pH of less than 5.0 (Yasar et al, 2016;Yasar and Gok, 2014). In these studies, it was shown that the fresh liquid whey could be used instead of water to yield the required amount of moisture content and citrus pomace as acidifying agent for lowering pH.…”
Section: Introductionmentioning
confidence: 99%